Healthy participant engagement in early clinical trials: results from the European EUFEMED survey - Klein, J.; van Iersel, T.; de Vries, D.; Donazzolo, Y.; Klingmann, I. (Frontiers in Pharmacology, 2025)
IntroductionWhile numerous healthy volunteers contribute to clinical trials on a yearly basis, the aspect of including these participants in the drug development process, like the patient-centric approaches, are not well known. To gain broader insights in the aspect of healthy participant engagement, preferences, and motivation, we performed a European wide survey. Additionally, a literature search on the topic of healthy participant engagement was performed.MethodsAn online questionnaire containing 61 questions on demographics, motivation, informed consent, engagement, transparency, and preferences was created, combining five-point Likert and open text field answers. The questionnaire was translated in several European languages and shared among early phase clinical trial units within Europe. Additionally, a literature search was performed on healthy participant engagement.ResultsA total of 4,349 completed questionnaires were eligible for analysis. Countries with adequate number of responses were Belgium, France, Netherlands, Germany, Hungary and United Kingdom. Altruistic motivation was the primary reason for participation. The Informed Consent Form (ICF) paragraphs on risk, schedule of assessments and restriction was better read than the financial aspects, ethics and data protection, with variations between gender, age, experience and country. Only 71.2% of the responders finds an ICF written in correct lay language and 44.6% is willing to assist in ICF review on adequate lay language. In the literature search, no articles described healthy participant engagement.DiscussionThe benefit of including patients in the drug development process has been proven in multiple publications and is a movement that is being advocated more frequently. Healthy participant engagement is not known yet, while similar benefits can be suggested. As altruistic reasons are the main motivation for participation, engaging participant in the clinical trials might enhance their motivation. Together with all stakeholders, description of methods for healthy participant engagement should be initiated to increase willingness to contribute to clinical trials.